Unconstrained nonlinear optimization - Chenna Nasreddine (My University, 2022)
ABSTRACT In this thesis we proved descent direction of the conjugate gradient method which is a combination convex of Fletcher and Reeves (FR) and Polak-Ribière and Polyak (PRP) method, and present a new hybrid method to solve an nonlinear unconstrained optimization problem by using conjugate gradient which is convex combination of Liu-Storey (LS) conjugate gradient method and Hager-Zhang (HZ) conjugate gradient method. This method possesses the sufficient descent property with Strong Wolfe-Powell line search and the global convergence with the Strong Wolfe-Powell line search. In the end of this thesis, we illustrate our method by giving some numerical examples. ------------------------------------------ RÉSUMÉ Dans cette thèse, nous avons prouvé la direction de descente de la méthode du gradient conjugué qui est une combinaison convexe de la méthode de Fletcher et Reeves (FR), et de la méthode de Polyak, Polak et Ribière (PRP). Et nous présentons une nouvelle méthode hybride pour résoudre un problème d’optimisation non linéaire sans contrainte, en utilisant une méthode de gradient conjugué qui est une combinaison convexe de la méthode du gradient conjugué Liu et Storey (LS), et de la méthode du gradient conjugué Hager et Zhang (HZ). La nouvelle méthode proposée vérifie la propriété de descente suffisante avec la recherche linéaire inexacte de Wolfe-Powell forte, et la globale convergence avec la recherche linéaire inexacte de Wolfe-Powell forte. À la fin de cette thèse, nous illustrons notre méthode en donnant quelques exemples numériques. ------------------------- في هذه الاطروحة أثبتنا أن موجه طريقة التدرج المترافق والتي هي مزيج محدب لطريقتي فليتشر- ريفز و بولاك ريبر بولياك موجه نزول. قمنا أيضا بعرض طريقة هجينة جديدة لحل مشكلة الأمثلة غير المقيدة وغير الخطية باستخدام التدرج المترافق وهي عبارة عن مزيج محدب من طريقة التدرج المترافق لوي- ستوري و طريقة التدرج المترافق هاجر – زانق . أثبتنا أن هذه الطريقة تحقق شروط التناقص الكافية بحث الحط غير الدقيق لووف – باول كما أثبتنا أيضا التقارب العام لهذه الطريقة مع بحث الخط غير الدقيق لووف – باول بشروطه القوية. في نهاية هذه الأطروحة وضحنا فعالية وكفاءة الطريقة المقترحة من خلال اعطاء بعض الأمثلة العددية.